A Novel Highly Selective Cannabinoid CB2 Agonist Reduces in vitro Growth and TGF-beta Release of Human Glial Cell Tumors - Cioni, Chiara; Tassi, Maristella; Marotta, Giuseppe; Mugnaini, Claudia; Corelli, Federico; Annunziata, Pasquale (Central Nervous System Agents in Medicinal Chemistry, 2019)
Background: Cannabinoid receptors have been detected in human gliomas and cannabinoids have been proposed as novel drug candidates in the treatment of brain tumors. Aims: To test the in vitro antitumor activity of COR167, a novel cannabinoid CB2-selective agonist displaying a high binding affinity for human CB2 receptors, on tumor cells isolated from human glioblastoma multiforme and anaplastic astrocytoma. Methods: Glioma cell cultures were established from two glioblastoma multiforme and two anaplastic astrocytomas. Proliferation was measured in the presence or absence of COR167 with a bromodeoxyuridine (BrdU) cell proliferation ELISA assay. CB2 receptor expression was detected by western blotting. Apoptosis was assessed with phycoerythrin (PE) annexin V flow cytometry kit. TGF-beta 1 and 2 levels were analyzed in culture supernatants with commercial ELISAs. Results: COR167 was found to significantly reduce the proliferation of both glioblastoma and anaplastic astrocytoma in a dose-dependent manner at lower doses than other known, less specific CB2 agonists. This activity is independent of apoptosis and is associated with a significant reduction of TGF-beta 1 and 2 levels in supernatants of glioma cell cultures. Conclusion: These findings add to the role of cannabinoid CB2 receptor as a possible pharmacological target to counteract glial tumor growth and encourage further work to explore any other pharmacological effect of this novel CB2 agonist useful in the treatment of human gliomas.
Keywords: cannabinoids